The Guidebook to Sociolinguistics - Bell, Allan (Wiley, 2013)
The Guidebook to Sociolinguistics presents a comprehensive introduction to the main concepts and terms of sociolinguistics, and of the goals, methods, and findings of sociolinguistic research.